"Imaginative? More Like Normative": Masculinities Depicted in Mune: Guardian of the Moon. Issue 1 (1st December 2022) - Moody, Jeana
Abstract: Mune: Guardian of the Moon is a children's animated film about a series of misadventures resulting in a lighthearted good-versus-evil plotline. This movie attempts to be imaginative and original, and succeeds in some ways, through positioning slight-figured, compassionate, shy Mune as the hero of the story and using dreams of transformation instead of fists to defeat evil. However, it falls short through its stereotypical depictions of masculinities and gendered dynamics. Rather than portraying diverse and alternate ways that masculinity can be performed, Mune utilizes normative gender roles and hegemonic masculinity to emphasize that even small, unassuming young men can adequately fulfill typical masculine leadership roles, so long as they are most powerful and ultimately win the girl.